Association between the Chinese Dietary Inflammatory Index and risk of gastric cancer: a case-control study in Southeastern China - Xinyu Chen; Yuhang Chen; Zhijie Luo; Lu Cheng; Qingying Wang; Fengqin Zou; Yulan Lin (Frontiers in Nutrition)
ObjectiveThis study aimed to investigate the association between the Chinese Dietary Inflammatory Index (CHINA-DII) and the risk of gastric cancer (GC) among adults in Fujian Province of China.MethodsA 1:1 matched case-control study was conducted between July 2023 and November 2024. A total of 336 newly diagnosed GC cases were recruited from the Union Hospital, and 336 sex-matched healthy controls were enrolled from communities in Fujian Province. Dietary data were collected using food frequency questionnaire (FFQ), and conditional logistic regression models were used to assess the association between CHINA-DII scores and GC risk.ResultsA total of 672 participants were included, comprising 336 GC cases and 336 controls. The proportions of males and females were 56.5 and 43.5%, respectively. The mean age of the case group was 56.76 ± 10.34 years, significantly higher than that of the control group (53.86 ± 11.13 years, P < 0.001). The average CHINA-DII score was −2.11 ± 0.62. Multivariable logistic regression analysis showed that higher intakes of vitamin C (OR = 0.69, 95% CI: 0.50–0.95) and vitamin D (OR = 0.67, 95% CI: 0.48–0.92) were significantly associated with lower GC risk. Higher CHINA-DII scores were positively associated with increased GC risk (OR = 1.45, 95% CI: 1.05–1.99), and each 1-standard-deviation increase in the CHINA-DII score was associated with a 1.26-fold increase in GC risk (OR = 1.26, 95% CI: 1.07–1.48). Subgroup analyses revealed significant positive associations between CHINA-DII and GC risk among individuals aged ≤ 55 years (OR = 2.44, 95% CI: 1.51–3.96), the married population (OR = 1.41, 95% CI: 1.01–1.96), non-smokers (OR = 1.70, 95% CI: 1.14–2.54), and those with high levels of perceived daily stress (OR = 2.82, 95% CI: 1.67–4.75).ConclusionLower intake of dietary vitamin C and vitamin D, as well as a higher overall dietary inflammatory potential, were significantly associated with an increased risk of GC. Younger, non-smoking, and those under greater psychological stress may be more sensitive to dietary inflammation.